Abrasion resistance analysis of coatings at electro-arc spraying using a pulsating spraying airflow - Zakharova, Iryna (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract. In the global practice of application, more than 50% are metal coatings applied by the method of electric arc metallization, which has the following advantages: high productivity, simplicity of equipment, low power consumption, the ability to 6obtaining coatings with high-performance properties through the use of scarce and inexpensive wires of industrial production. But the main drawback is the process of oxidation of alloying elements during transportation of molten electrode particles by spraying airflow. A series of scientists’ works are aimed at improving the design of spray heads of electric arc metallizers, which involves improving the design of the air nozzle through the use of inserts and devices providing a change in the spraying airflow, and leads to a significant increase in the price of the process. To reduce the oxidizing effect of the spraying airflow on the liquid metal of the electrodes the method of pulsating air injection into the electrode melting zone has been developed. This paper presents the influence of the pulsating spraying flow on the indicators of abrasive wear and reduction of oxidation of metal particles, at the arc metallization to obtain coatings with the specified properties and application of resource-saving.